Financial market bubbles and crashes - Vogel, Harold L. , 1946- (Cambridge University Press, 2010)
"Despite the thousands of articles and the millions of times that the word 'bubble' has been used in the business press, there still does not appear to be a cohesive theory or persuasive empirical approach with which to study 'bubble' and 'crash' conditions. This book presents a plausible and accessible descriptive theory and empirical approach to the analysis of such financial market conditions. It advances such a framework through application of standard econometric methods to its central idea, which is that financial bubbles reflect urgent short side rationed demand. From this basic idea, an elasticity of variance concept is developed. It is further shown that a behavioral risk premium can probably be measured and related to the standard equity risk premium models in a way that is consistent with conventional theory"--Provided by publisher